Functional damage of endothelial progenitor cells is attenuated by 14‐3‐3‐n through inhibition of mitochondrial injury and oxidative stress. (25th December 2020) - Li, Yunde; Sun, Xinglan; Zhang, Xuemei; Zhou, Hui; Wang, Dan; Xia, Yi; Li, Xiuli
Abstract: Endothelial progenitor cells (EPCs) are precursor cells of vascular endothelial cells, which are widely involved in the pathological process of cardiovascular diseases. EPCs apoptosis could accelerate the process of cardiovascular diseases. 14‐3‐3‐η protein has been proved to be a potent antiapoptosis molecule. However, inhibition of EPCs apoptosis by 14‐3‐3‐η and further specific mechanism have not been investigated. EPCs were isolated from human cord blood, and identified using VEGFR2 and CD34. 14‐3‐3‐η overexpression model in vitro was established. Cell invasion, apoptosis, and proliferation were measured by transwell, flow cytometry, and Cell Counting Kit‐8, respectively. Expression of 14‐3‐3‐η, Bcl‐2, and voltage‐dependent anion channel 1 (VDAC1) were measured using quantitative real‐time polymerase chain reaction and western blot analysis. Reactive oxygen species (ROS) intensity was measured using 2ʹ‐7ʹ dichlorofluorescin diacetate probe. Mitochondrial membrane potential was detected using JC‐1 dye. Overexpression of 14‐3‐3‐η significantly promoted invasion and proliferation, but suppressed apoptosis of EPCs. Overexpression of 14‐3‐3‐η remarkably inhibited ROS and promoted antioxidant enzyme levels in EPCs. 14‐3‐3‐η might inhibit apoptosis of EPCs through attenuating mitochondrial injury. This study might provide a new target, 14‐3‐3‐η, for the prevention and treatment of cardiovascular diseases through targeting EPCs.